De quelle régulation la notion de « zone grise d’emploi » est-elle le nom ? - Patrick Dieuaide (Revue Interventions Économiques)
The notion of "employment grey zone" is not unknown to labor economists. It is found in numerous articles to highlight the persistence of informal or illegal employment, especially in emerging countries. The article takes up this notion and discusses its merits with regard to the presence of the phenomenon at the heart of the employment relationship of the major economies of advanced capitalism. The notion of employment grey zone is not considered as a dysfunction of the legal rules that frame the employee / employer relationship but as a structural feature characteristic of a new cartography of power relations closely linked to value chains, strategy and management policies of the FMNs. Considering the case of France, the notion of "social regulation without compromise" is advanced and discussed in order to underline the importance of “employment grey zones” in the implementation of a managerial regulation of the social dialogue and the employment relationship.